Evaluation of genetic instability of short tandem repeats in hepatocellular carcinoma - Yinghui Song; Ming Xu; Yufeng Li; Xinling Zhang; Wei Xu (Scientific Reports)
Abstract Hepatocellular carcinoma (HCC) ranked as the sixth most common malignancy and the third leading cause of cancer-related mortality with approximately 830, 000 deaths worldwide annually. Genetic instability of short tandem repeats (STRs), which manifested as loss of heterozygosity (LOH) or microsatellite instability (MSI) in the cancerous cells, is a genetic feature of many types of human cancers. The status of STR instablility and its clinical significance in HCC, however, remains to be comprehensively elucidated. In this study, a total of 101 matched DNA samples from HCC individuals were analyzed with 20 “classical STR markers widely used in forensic genetics, our findings demonstrated that 79.21% (80/101) of HCC cases exhibited genetic alterations in at least 1 STR locus, with 16.73% of STR loci altered across all samples. Moreover, our findings also revealed a significant association between an accumulation of STR alterations and the presence of positive hepatitis B surface antigen (HBsAg), as well as moderate-poor/poor differentiation of HCC. Furthermore, LOH at the FGA was found to be significantly correlated with moderate-poor/poor differentiation of HCC (p = 0.002), and LOH at the D16S539 was found to be significantly associated with elevated serum levels of AFP (p = 0.042) as well as larger tumor sizes (p = 0.040). Overall, this study contributes valuable insights into the genetic instability of STRs in HCC and might also enhance insights into the intricate mechanisms underlying hepatocarcinogenesis.